Decadal change in summer precipitation over the east of Northwest China and its associations with atmospheric circulations and sea surface temperatures. (18th December 2019) - Shang, Shasha; Zhu, Gaofeng; Li, Ruolin; Xu, Jie; Gu, Juan; Chen, Huiling; Liu, Xiaowen; Han, Tuo
Abstract: As global warming has progressed, precipitation patterns over arid Northwest China have undergone significant change. In this study, changes in summer (JJA) precipitation over the eastern part of Northwest China (ENWC) from 1980 to 2014 were investigated using the China gridded monthly precipitation dataset (CN05.1). The results showed that summer precipitation over the ENWC experienced a decadal wet‐to‐dry shift in 1998. Westerlies played an important role in the upper atmospheric levels in terms of water vapour transport; the decadal variations in summer precipitation were principally controlled by the water vapour input from the ENWC's western boundary. In addition, the decadal variations in summer precipitation in the ENWC appear to be associated with a meridional teleconnection around 110°E and a zonal pattern over 45–60°N in the lower troposphere. These two teleconnections led to cyclonic anomalies in the ENWC and enhanced water vapour transport into the ENWC, resulting in above‐normal precipitation during the 1989–1998 decadal period. Further, the warmer (colder) sea surface temperatures (SSTs) observed in the tropical Eastern Pacific correspond to the southward (northward) displacement of the Asian jet stream and a negative (positive) phase of the Silk Road pattern, resulting in a wet (dry) ENWC. Moreover, the SST anomalies in the North Atlantic and Northwest Pacific may affect summer precipitation over the ENWC via a zonal teleconnection in the middle troposphere. Abstract : Schematic diagram of major atmosphere circulation mechanisms for the wet period (top) and the dry period (bottom) over the ENWC. "+" and "−" represent the positive and negative geopotential height anomalies at 500 hPa; "AC" and "C" stand for "anticyclone" and "cyclone", respectively. The blue arrows represent the wind direction in the lower troposphere.